2021
DOI: 10.1097/mjt.0000000000001403
|View full text |Cite
|
Sign up to set email alerts
|

Direct Oral Anticoagulants Versus Warfarin in Morbidly Obese Patients With Nonvalvular Atrial Fibrillation: A Systematic Review and Meta-analysis

Abstract: Background: Direct oral anticoagulants (DOACs) have been increasingly preferred over warfarin; however, The International Society of Thrombosis and Hemostasis recommended avoiding the use of DOACs in morbidly obese patients (body mass index >40 or weight >120 kg) because of limited clinical data. Study Question: Are DOACs effective and safe in morbidly obese patients with nonvalvular atrial fibrillation (NVAF). Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 31 publications
(58 reference statements)
2
10
0
Order By: Relevance
“…Was not based on patients with AF (7); Duplicated studies (21). Finally, only 10 studies [11][12][13][14][15][16][17][18][19][20] were selected to be used for this meta-analysis.…”
Section: Searched Outcomesmentioning
confidence: 99%
“…Was not based on patients with AF (7); Duplicated studies (21). Finally, only 10 studies [11][12][13][14][15][16][17][18][19][20] were selected to be used for this meta-analysis.…”
Section: Searched Outcomesmentioning
confidence: 99%
“…55 All of the other systematic reviews involving patients with varying degrees of obesity found DOACs to yield similar or better outcomes compared with warfarin in terms of VTE and major bleeding events. [56][57][58][59][60][61][62][63] However, as exemplified by one of the more recent systematic reviews, 63 the certainty of evidence underlying outcome comparisons was typically defined as low or very low, as the majority of included studies were observational or post hoc analyses of randomized trials. Detailed information related to specific DOACs and dosing regimens was not provided likely due to the lack of such data in the studies under review.…”
Section: Systematic Reviewsmentioning
confidence: 99%
“…Since that recommendation, several studies and post-hoc analyses have investigated the impact of BMI on the safety and effectiveness DOACs, including Dabigatran, Rivaroxaban, Apixaban, and Edoxaban [ 11 16 ]. A systemic review and meta-analysis including a total of 89,494 morbidly obese patients with non-valvular AF comparing DOACs to warfarin reported that DOAC was associated with significantly lower stroke or systemic embolism [odds ratio (OR): 0.71; 95% confidence interval (CI): 0.62–0.81; P < 0.0001; I 2 = 0%] compared to warfarin [ 17 ]. In addition, DOACs had a significantly lower major bleeding compared to warfarin (OR: 0.60; 95% CI: 0.46–0.78; P < 0.0001; I 2 = 86%) [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…A systemic review and meta-analysis including a total of 89,494 morbidly obese patients with non-valvular AF comparing DOACs to warfarin reported that DOAC was associated with significantly lower stroke or systemic embolism [odds ratio (OR): 0.71; 95% confidence interval (CI): 0.62–0.81; P < 0.0001; I 2 = 0%] compared to warfarin [ 17 ]. In addition, DOACs had a significantly lower major bleeding compared to warfarin (OR: 0.60; 95% CI: 0.46–0.78; P < 0.0001; I 2 = 86%) [ 17 ]. A sub-class analysis in that meta-analysis showed that apixaban and rivaroxaban were superior to warfarin in safety and efficacy [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation